Cardiovascular ion channels as a molecular target of flavonoids - Scholz, Eberhard P.; Zitron, Edgar; Katus, Hugo; Karle, Christoph (Cardiovascular therapeutics, 2010)
Flavonoids are a class of naturally occurring polyphenols abundant in edibles and beverages of plant origin. Epidemiological studies consistently associate high flavonoid intake with a reduced risk for the development of cardiovascular diseases. So far these beneficial effects have been mainly attributed to nonspecific antioxidant and antiinflammatory properties. However, there is an increasing body of evidence that flavonoids specifically target molecular structures including cardiovascular ion channels. Playing a pivotal role in the regulation of vascular tone and cardiac electric activity, ion channels represent a major target for the induction of antihypertensive and cardioprotective effects. Thus, pharmacological properties of flavonoids on cardiovascular ion channels, ion currents and tissue preparations are being increasingly addressed in experimental studies. Whereas it has become clear that cardiovascular ion channels represent an important molecular target of flavonoids, the published data have not yet been systematically reviewed.
Gesehen am 28.06.2023